A cost-effectiveness analysis comparing pembrolizumab combined with chemotherapy versus chemotherapy alone for advanced biliary tract cancer: US and China perspectives - Chunhua Zhang; Hua Liang; Yanni Qin; Xiaolan Tan; Xiaoqing Su; Xin Tian; Yumei Nong (PLoS ONE, 2026)
Objective In the KEYNOTE-966 study, the clinical benefits of pembrolizumab plus chemotherapy were demonstrated for patients with advanced biliary tract cancer (BTC). At this point, it is unknown whether this expensive therapy is cost-effective. The purpose of this study was to evaluate the cost-effectiveness of pembrolizumab plus chemotherapy in treating BTC. Methods We constructed a partitioned survival model form the perspectives of US and Chinese payers. KEYNOTE-966 was used to obtain the baseline characteristics of the patients as well as their clinical data. Local databases and published literature were used to collect costs and utilities. Costs, life years, quality-adjusted life years (QALYs), incremental cost-effectiveness ratios (ICERs), incremental net health benefits (INHB), and incremental net monetary benefits (INMB) were measured and compared. We conducted sensitivity analyses in order to assess the robustness of the model. Subgroup analyses were also performed. Results Pembrolizumab plus chemotherapy is not cost-effective in China at the willingness to pay (WTP) thresholds of $38,258 and $84,866. However, it yielded an additional 0.137 QALYs and an additional $63,864 (ICER $466,340) over chemotherapy alone. In the US, this treatment was not cost-effective, resulting in an improvement in effectiveness of 0.144 QALYs and an increase in overall cost of $141,000 (ICER of $976,925). There were INHBs of −0.616 QALYs and INMBs of -$52,237 for pembrolizumab plus chemotherapy in China if the WTP threshold for QALYs was set at $84,866, and INHBs of −0.796 QALYs and INMBs of -$119,400 when the WTP threshold was set at $150,000 for the US. Through sensitivity analyses, it was demonstrated that the results were stable. The results of the subgroup analysis indicate that better survival properties subgroups were more likely to be cost-effective, although pembrolizumab plus chemotherapy may not be cost-effective for all subgroups. Conclusions In the US and China, pembrolizumab plus chemotherapy may not be a cost-effective treatment option. This study provides evidence-based pricing strategies that may benefit decision makers and clinicians as they make clinical decisions. For a better understanding of the impact on budgets and the affordability of care for patients, more evidence is required.